2011
DOI: 10.1124/mol.111.075804
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Smooth MuscleS-Nitrosylproteome in Pregnancy

Abstract: The molecular mechanisms involved in uterine quiescence during gestation and those responsible for induction of labor are not completely known. Nitric oxide relaxes uterine smooth muscle in a manner disparate from that for other smooth muscles because global elevation of cGMP after activation of soluble guanylyl cyclase does not relax the muscle. S-Nitrosylation, the covalent addition of an nitric oxide (NO) group to a cysteine thiol is a likely mechanism to explain the ability of NO to relax myometrium. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Among the microtubule motors, only kinesin has been found to be S-nitrosylated (Abat et al, 2008;Ulrich et al, 2012). The functional effects of that S-nitrosylation are unknown.…”
Section: Motor Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the microtubule motors, only kinesin has been found to be S-nitrosylated (Abat et al, 2008;Ulrich et al, 2012). The functional effects of that S-nitrosylation are unknown.…”
Section: Motor Proteinsmentioning
confidence: 99%
“…S-nitrosylation of myosin heavy and light chains in intact cardiac myofibrils correlates with a decrease in ATPase activity (Figueiredo-Freitas et al, 2015); the authors of that study suggested Cys191 on myosin light chain 3 as the potential causative factor. The heavy chains of some unconventional myosin isoforms have also been found to be nitrosylated, but the functional impacts of S-nitrosylation of these isoforms are unknown (Abat et al, 2008;Batool et al, 2017;Greco et al, 2006;Kohr et al, 2011;Shi et al, 2008;Ulrich et al, 2012). The heavy chains of some unconventional myosin isoforms have also been found to be nitrosylated, but the functional impacts of S-nitrosylation of these isoforms are unknown (Abat et al, 2008;Batool et al, 2017;Greco et al, 2006;Kohr et al, 2011;Shi et al, 2008;Ulrich et al, 2012).…”
Section: Motor Proteinsmentioning
confidence: 99%
“…The pathway through which NO relaxes the myometrium independent of cGMP is unknown, but it is likely that the S-nitrosation of contractile proteins plays a role. It has been determined that the state of labor (full term vs. preterm) can vastly alter the S-nitrosated protein landscape in uterine smooth muscle after exposure to GSNO (Ulrich et al, 2012). It is also well known that S-nitrosation can vary significantly based upon the cytoplasmic availability GSNOR (Broniowska and Hogg, 2012; Hess et al, 2005; Thomas and Jourd’heuil, 2012).…”
Section: Gsnor Dysregulationmentioning
confidence: 99%
“…Combined with the observation that GSNOR inhibition causes relaxation of murine aortic rings[91], these results suggest that increased levels of protein S-nitrosylation are associated with improved vasodilation and lower blood pressure. Multiple possible targets of S-nitrosylation have been identified in smooth muscle, including structural and contractile proteins[92, 93]. For example, the direct activation of VSMC Ca 2+ -dependent K + channels by S-nitrosylation[94] was proposed as a potential mechanism of cGMP-independent vasorelaxation[95].…”
Section: Sgc-independent Effects Of No: Role Of Protein S-nitrosylatimentioning
confidence: 99%